Професійний бейсбол, сумо та Джей-ліга: минуле і сучасність - Сано Масафумі (Народна творчість та етнографія, 2009)
The article is about the history of development of the professional kinds of sport in Japan. The most wide-spreasad are examined: Sumo history' of more than 13 Centuries history, baseball, and football and influence of the social-economic factors on them.